The Effect of Various Factors on the Resistance and TCR of RuO2 Thick Film Resistors—Relation Between the Electrical Properties and Particle Size of Constituents, the Physical Properties of Glass and Firing Temperature. (1988) - Abe, Osamu; Taketa, Yoshiaki; Haradome, Miyoshi
Abstract : Thick film resistors were prepared with different variables, they included various conductive particle sizes, glass particle sizes, glass softening temperatures, thermal expansion coefficients of the glass, mixing ratios of the conductive element and glass, firing temperatures, firing cycles, etc. The relation between these factors and electrical properties of the thick film resistors was studied. As a result, it was found that when a specific glass is chosen, its R-TCR curve, which indicates the relation between resistance and TCR of a thick film resistor, is unconditionally fixed regardless of various preparation factors, and the R-TCR curve can be moved only by changing the thermal expansion coefficient of the glass. In addition, the higher the resistance and the larger the thermal expansion coefficient of glass, the larger the resistance change against the external force.